Context in Functional Discourse Grammar - Connolly, John H. (ALFA: Revista de Linguística, 2009)
An important and admirable characteristic of the FDG framework is that it takes very seriously the fact that utterances are produced and understood in context. Given this fact, the aim of the present paper is to articulate, in more detail than hitherto, how context may be treated and described within FDG, and to provide FDG with a more comprehensive contextual framework than has previously been available. At the beginning of the paper some general principles of context are established. It is then shown how context may be internally categorised, to reveal a complex multidimensional structure. In the light of this, a modified version of the FDG framework is proposed. The proposed model is then applied to the functional description of some aspects of Modern English, with a view to showing how the application of the framework enables a more analytical and perspicuous description of the pragmatics involved. The areas illustrated are constituent order, fragmentary text, clauses with unexpressed elements, and the inferencing of information. It is concluded that the framework makes possible a more exact and detailed treatment of the role played by context in language-use than would otherwise be feasible.